Enzymatic soy protein hydrolysis: A tool for biofunctional food ingredient production - Coscueta, ER (2019)
This work aimed to evaluate the digestive stability of the peptides previously identified from a Corolase PP soy protein hydrolysate (SPH) and to respond to the uncertainty about the merit of controlled hydrolysis. For this purpose, we applied an empirical and theoretical analysis, determining peptide sequences, oxygen radical scavenging (ORAC) and ACE inhibitory (iACE) activities, and the effect of hydrolysis on solubility. Results showed that during digestion most of SPH peptides were degraded as smaller ones. However, both SPH bioactivities improved significantly after digestion (3.9 ± 0.1 µmol TE/mg protein for ORAC and IC 50 = 52 ± 4µg protein/mL for iACE) with similar values for soy protein isolate (SPI). With respect to solubility, the controlled hydrolysis considerably increased this functional property. In conclusion, the results indicated that controlled enzymatic hydrolysis of SPI with Corolase PP produced an ingredient more apt to be incorporated in certain nutritional or nutraceutical formulations.